Utopia? Tak, poproszę! - Bednarek, Joanna (Praktyka Teoretyczna, 2011)
Recenzja: Weeks Kathi. 2011. The Problem with Work: Feminism, Marxism, Antiwork Politics, and Postwork Imaginaries. Duke Univeristy Press.